Determinants of Taxpayer Compliance: The Moderating Role of Digital Literacy - Dianita Nur Lailiyah; Mia Ika Rahmawati (Politeknik Ganesha Medan, 2026)
This research is motivated by Indonesia's low tax ratio, which remains below the average for ASEAN and OECD countries. Therefore, optimizing taxpayer compliance is necessary amidst the digital transformation of the tax system. Therefore, the purpose of this study is to examine the influence of tax knowledge, morality, and tax awareness on taxpayer compliance, and to assess the role of digital literacy as a moderating variable. Using a quantitative approach, this study involved 95 individual taxpayer respondents at the Gresik Medium Tax Office (KPP Madya) selected through purposive sampling. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results concluded that tax knowledge, morality, and tax awareness had a positive and significant effect on taxpayer compliance. As for the moderating variable, digital literacy was shown to strengthen the influence of morality and tax awareness on compliance. However, digital literacy did not moderate the influence of tax knowledge, as understanding the rules is a fundamental factor whose effect remains stable across levels of digital capability. Overall, improving compliance requires integrating and strengthening taxpayers' internal values with proficiency in modern tax technology systems.